Research on the technology of producing polymer composition based on recycled polyamides and polyphthalamide with enhanced properties - Yekymov, Yevhen; Tomilin, Oleksandr; Lebedev, Vladimir (National Technical University "Kharkiv Polytechnic Institute", 2025)
A low-temperature method for recycling PPA waste via pulverization and blending with PA6,6 is proposed. The approach avoids full melting, cuts energy use, and preserves mechanical properties. Resulting composites show enhanced strength and industrial applicability.
Keywords: PPA recycling; pulverization; PA66; low-temperature processing; unmolten phase